Model Supervisi Transformasional Model Supervisi Transformasional untuk Mendorong Inovasi Pendidikan di Sekolah Dasar Islam Terpadu (SDIT) Al Ikhlas Kabupaten Cirebon - Mahmudah, Yuyun Widara, Wafiq Fadhilah Anwar, Siti (Invention: Journal Research and Education Studies, 2024)
This research describes an effective transformational supervision model for making changes to encourage educational innovation in the Integrated Islamic Elementary School (SDIT) Al Ikhlas Cirebon Regency, aiming to achieve real success. Method: The research employs a qualitative approach using a case study research method. The subjects in this research include supervisors, teachers, and principals involved in the transformational supervision programs in schools. Data collection is conducted through interviews, documentation, and observation. Data analysis adopts an inductive and thematic approach to identify emerging patterns and findings. The research results confirm that the Transformational Supervision Model is a powerful approach for driving educational innovation in primary schools. By engaging educational leaders who play a critical role in supporting and inspiring teachers, this model creates a supportive and motivating environment for innovative learning practices. As a result, it improves the quality of education, develops relevant student skills, and prepares them for the future to meet the demands of the global society. Keywords : Innovation, Integrated Islamic Elementary School Education (SDIT), Transformational Supervision